Subjective workload, professional environment and job satisfaction of anesthesia and intensive care nurses: a cross-sectional survey study - Žydžiūnaitė, Vilma; Mickevičiūtė, Viktorija (Frontiers in Public Health, 2025)
BackgroundThere are studies that reveal the relationship between workload and job satisfaction, studies that would examine workload, professional environment, and job satisfaction separately, but there is still lack of the empirical evidence which proves various combinations between all these mentioned variables internationally within the anesthesia and intensive care nursing community.AimThis study aimed to analyze the relationship between anesthesia and intensive care nurses’ subjective workload, professional environment, and job satisfaction.Methods149 anesthesia and intensive care nurses working in the clinical hospitals of one county of Lithuania participated in the study. NASA Task Load Index (NASA-TLX), The Practice Environment Scale of the Nursing Work Index, and The Questionnaire of the Relation Between Job Satisfaction and Workload were used for data collection. IBM Statistical Package for Social Sciences Statistics for Windows, version 29.0 was used for data analysis.ResultsAnesthesia and intensive care nurses experience above average or high subjective workload and rate their professional environment and job satisfaction as average. Nurses who experience higher subjective workload experience lower job satisfaction. Similarly, nurses who work in a more favorable professional environment experience lower workload and higher job satisfaction. The highest job satisfaction is among anesthesia and intensive care nurses who experience average workload and rate their professional environment positively. With high workload and unfavorable professional environment, anesthesia and intensive care nurses’ job satisfaction decreases.ConclusionThere is a relationship between anesthesia and intensive care nurses’ workload, professional environment and job satisfaction, regardless of geographical boundaries or different locations, the structure of the healthcare system, and these factors constantly affect each other. Subjective workload, work environment, and job satisfaction of anesthesia and intensive care nurses are interrelated and influence each other. Nurses who work in an unfavorable environment without managerial support, collaboration, and teamwork experience higher workload and lower job satisfaction. This means that job satisfaction decreases when there is a high workload and an unfavorable work environment.